2021
DOI: 10.1055/s-0041-1729454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigating Agitation after Root End Preparation on the Wall Cleaning and Bond Strength of Calcium Silicate Material in Retrograde Obturation

Abstract: Objective The study aimed to evaluate the cleaning efficacy of irrigant activation with a new ultrasonic tip in root-end preparations and to determine its influence on the bond strength of calcium silicate-based material. Materials and Methods Maxillary canines were prepared and filled, and their root ends resected. Root-end cavities were ultrasonically prepared and randomly distributed into four groups according to the final irrigation protocols: G1 (ultrasonic irrigation [UI] + saline solution [SS]), G2 (syr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…This nding is in line with those of Gokturk et al who similarly stated that a signi cant increase in dislocation resistance of MTA Flow and MTA Angelus was found following application of 17% EDTA compared to chitosan-based silver nanoparticles (AgNPs-chitosan), and maleic acid (17). Consistently, Valencia et al stated that 17% EDTA was able to improve PBS of calcium silicate cement to dentin when used as a retro-lling material (42). This was also supported by Ballal et al who reported that use of 17% EDTA as an irrigation solution could increase PBS of Biodentine (20).…”
Section: Discussionsupporting
confidence: 88%
“…This nding is in line with those of Gokturk et al who similarly stated that a signi cant increase in dislocation resistance of MTA Flow and MTA Angelus was found following application of 17% EDTA compared to chitosan-based silver nanoparticles (AgNPs-chitosan), and maleic acid (17). Consistently, Valencia et al stated that 17% EDTA was able to improve PBS of calcium silicate cement to dentin when used as a retro-lling material (42). This was also supported by Ballal et al who reported that use of 17% EDTA as an irrigation solution could increase PBS of Biodentine (20).…”
Section: Discussionsupporting
confidence: 88%
“…This may be a possible explanation for the higher bond strength of the tested EndoSeal MTA sealer in the current study. 36 The push-out bond strength of the EndoSeal MTA sealer was significantly less for phosphoric acid than for 17% EDTA and 7% maleic acid, which could be explained by the demineralization ability of the phosphoric acid being time dependent. 37 The results showed greater bond strength for the AH Plus sealer than the EndoSeal MTA sealer when comparing both EndoSeal MTA and AH Plus sealers in terms of the push-out bond strength, as shown in ►Table 2.…”
Section: Discussionmentioning
confidence: 91%
“…This may be a possible explanation for the higher bond strength of the tested EndoSeal MTA sealer in the current study. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Then, after performing a standard retro preparation with retro tip and saline solution, a small ultrasonic tip 25.02 activates EDTA and NaOCl gel to ensure deeper cleaning. Another research [ 23 ] evaluated the activation of EDTA alone and showed great results. Instead, in this work, in addition to the use of EDTA, NaOCl gel was also added.…”
Section: Discussionmentioning
confidence: 99%